PENGENDALIAN BANJIR DAS DOLOK – PENGGARON PADA SUNGAI BABON - Choirul, David; Kusuma, Rienddy Fajar; Wahyuni, Sri Eko; Darsono, Suseno (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Flood is a condition where areas that normally are not inundated by water such as settlements, and other public facilities become stagnant. The impact of flood disasters is very detrimental both morally and materially as delays in transport lines which impact on the pace of the economy. Semarang city is one of the areas in Indonesia are prone to flooding. The condition worsened with a decrease in the land throughout the year reached 0.7 to 11.2 cm / year. Starting from Ivory Pucang weir, river silting baboon suffered due to sedimentation, thereby reducing the capacity of water drainage caused flooding in the area around the river. This study using HEC-HMS software to analyze the flood discharge with a return period of 2, 5, 10, 25, 50 and 100 years. From some of the return period flood discharge plan, for further analysis taken flood discharge plan with a return period of 100 years. The program has been calibrated using the flood discharge at the dam hourly Pucang Ivory. HEC-HMS addition, this study also uses the HEC-RAS software to analyze the profile of the river water level and produce a flood inundation area of flood discharge plan with a return period of 100 Pathe obtained from the processing of data for flood inundation in the area Sayung, Kab. Demak, so the need to improve cross-section.